Wskazówki dotyczące wychowywania w rodzinie prezentowane na łamach czasopism w XIX wieku - Okrasa, Marzena (Karkonoska Państwowa Szkoła Wyższa, 2011)
The article presents tips on raising children published in journals in the nineteenth century. Their role was to educate parents. In many publications it was written literally, that parents, especially mothers, have no grounds for raising children. Therefore, the information contained in the texts related to educational culture, health behavior, moral education, the formation of character and mind. The authors marked that more parents should take care of the health aspects, namely to improve living conditions, hygiene of everyday life, as well as adopt attitudes and behaviors conducive to health. They urged the need of kneading in the children a strong will to prevent them in future from unexpected events and non-permanent fate. They drew attention to the need for mental development. It was believed that it is important notonly what features will develop, but also what your child will learn. Knowledge should be presented as a boon, human dignity, which puts him on a higher level of existence. Particular attention is paid to the social upbringing, noting that the more there will be good people in the world, the more this will override good intentions and noble aspirations. The desire for happiness is the reason for care to be taken of the education of children.
Keywords: edukacja; rodzice; rodzina; czasopisma